Pendampingan Program Penguatan Pendidikan Karakter Melalui Pembiasaan Atikan Nyucikeun Diri Di SDN 2 Mekarjaya - Ramdani, Fazri; Oktriawan, Wawan; Supendi, Dede (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2025)
Character education is a fundamental aspect in the personal formation of learners in order to build individuals with noble character, integrity, and responsibility. However, the reality in the field shows a moral crisis among students. One of the solutions implemented is the Atikan Nyucikeun Diri program at SDN 2 Mekarjaya, Purwakarta. This program aims to instill religious and moral values through worship habits such as Dhuha prayer, prayer and tawasul, recitation of Surah Yasin, and character education tausyiah. This research uses the Participatory Action Research (PAR) method with the stages of planning, action, observation, and reflection. Data were collected through observation, interviews, mentoring, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that the Atikan Nyucikeun Diri program has a positive impact in shaping the character of students, such as increasing awareness of worship, discipline, responsibility, and politeness in social interactions. The program also helps to create a more harmonious and religious school environment. With consistent habituation, the program is expected to become an effective and sustainable model of local wisdom-based character education.